Perioperative analgesic efficacy of bilateral superficial cervical plexus block in patients undergoing thyroidectomy: a randomized controlled trial - Karakış,Alkan (2019)
Abstract Introduction: Bilateral superficial cervical plexus block (BSCPB) is a common method used for analgesia in thyroid surgery. We investigated the analgesic efficacy of bilateral superficial cervical plexus block in the intraoperative and postoperative periods. Materials and methods: Patients (n = 46) undergoing thyroidectomy were randomly separated into the following 2 groups: the general anesthesia group (GA; n = 23) and the general anesthesia plus BSCPB group (GS; n = 23). The intraoperative analgesic requirement (remifentanil) and visual analog scale (VAS) score at multiple time points during the postoperative period (after extubation, at 15 , 30 minutes and 1, 2, 6, 12, 24, and 48 hours post operation) were evaluated. Total tramadol and paracetamol consumption as well as the amount of ondansetron used was recorded. Results: The intraoperative remifentanil requirement was significantly lower in the GS Group than in the GA Group (p= 0.009). The postoperative pain scores were significantly lower in the GS Group than in the GA Group at 15 (p< 0.01), 30 (p< 0.01) minutes, and 1 (p< 0.01), 2 (p< 0.01), 6 (p< 0.01), 12 (p< 0.01) and 24 (p= 0.03) hours. The postoperative tramadol requirement was significantly lower in the GS Group than in the GA Group (p= 0.01). The number of patients that used ondansetron was significantly lower in the GS Group than in the GA Group (p= 0.004). Conclusion: We concluded that BSCPB with 0.25% bupivacaine reduces the postoperative pain intensity and opioid dependency in thyroid surgery patients.